2010
DOI: 10.1007/s11596-010-0366-z
|View full text |Cite
|
Sign up to set email alerts
|

TNFR 2 M196R polymorphism and acne vulgaris in Han Chinese: A case-control study

Abstract: In this case-control study, the relationship between M196R (676 T-->G) variant in exon 6 of tumor necrosis factor receptor type 2 (TNFR2) gene and genetic susceptibility of acne vulgaris in Han Chinese was investigated. A total of 93 acne vulgaris patients and 90 healthy subjects from Han Chinese ethnic group were enrolled in this study. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique was adopted to analyze the single nucleotide polymorphisms (SNPs) of TNFR2 M196R gene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Research in the Chinese population has further demonstrated that familial factors are involved in the etiopathogenesis of acne vulgaris in the Chinese population [1,24]. In previous studies, the candidate gene selection focused on inflammatory reactions-related genes [26,27,28] and androgen-related genes [7,12,13]. …”
Section: Discussionmentioning
confidence: 99%
“…Research in the Chinese population has further demonstrated that familial factors are involved in the etiopathogenesis of acne vulgaris in the Chinese population [1,24]. In previous studies, the candidate gene selection focused on inflammatory reactions-related genes [26,27,28] and androgen-related genes [7,12,13]. …”
Section: Discussionmentioning
confidence: 99%
“…66 In 2010, heterozygous mutations were reported in the c-secretase genes PSENEN, PSEN1 and NCSTN in six Chinese multiplex kindreds, all showing full cosegregation. 67 One of these genes, NCSTN, lies within the previously reported region of linkage on chromosome 1. 66 Mutations have since been reported in two British, six Chinese, one Japanese and three French multiplex kindreds, as well as four apparently sporadic cases.…”
Section: Geneticsmentioning
confidence: 93%
“…Until about 10 years ago, only one putative genetic locus had been reported in HS (a 80‐cM locus on chromosome 1 1p21·1–1q25·3) . In 2010, heterozygous mutations were reported in the γ‐secretase genes PSENEN , PSEN1 and NCSTN in six Chinese multiplex kindreds, all showing full cosegregation . One of these genes, NCSTN , lies within the previously reported region of linkage on chromosome 1 .…”
Section: Pathogenesismentioning
confidence: 96%
See 2 more Smart Citations